2020
DOI: 10.1002/eng2.12062
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oxygen transport in microfluidic bioreactors for cell culture and organ‐on‐chip applications

Abstract: In the recent decade, development of microfluidic bioreactors and organ-onchip platforms for drug screening and disease modeling has been rising significantly. Prediction of oxygen level within the microfluidic bioreactors to create physiologically relevant oxygen tension for realistic cellular behavior is of critical importance. This article presented an analytical method to calculate oxygen tension in microchannel parallel plate bioreactors. Two-dimensional convection-diffusion equation was solved analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…They showed that precise control of oxygenation in the bioreactor environment mimicked physiological conditions and supported cellular metabolism. This study emphasized the significance of maintaining sufficient oxygen levels for promoting proper cellular function and tissue development [279].…”
Section: Bioreactorsmentioning
confidence: 90%
“…They showed that precise control of oxygenation in the bioreactor environment mimicked physiological conditions and supported cellular metabolism. This study emphasized the significance of maintaining sufficient oxygen levels for promoting proper cellular function and tissue development [279].…”
Section: Bioreactorsmentioning
confidence: 90%
“…[ 102 ] A typical workflow of numerical simulation involves problem definition, modeling, discretization, boundary setting, numerical solution, and post‐processing. Numerical simulation techniques help eliminate the need to repeat experimental measurements (e.g., shear stress [ 103 ] and oxygen distribution [ 104 ] ) and allow the optimization of iOOC systems at a lower cost. [ 105 ] Further, these techniques can improve the understanding of the physical phenomena and tissue behaviors in the microenvironment of iOOC systems.…”
Section: Data Processing For Iooc Systemsmentioning
confidence: 99%
“…For applications which require lower oxygen levels a commonly used method is to reduce the partial pressure of atmospheric oxygen with technology such as hypoxic chambers. Alternatively reductions in oxygen delivery to media, either actively through the control of flow rates or passively through oxygen-permeable membranes, can be another useful tool particularly if access to a gas supply is limited [ 138 , [141] , [142] , [143] , [144] ]. This leads to wide variability in the effectiveness of oxygenation systems and characterisation of oxygenation levels is important if results can be accurately replicated [131] .…”
Section: Fluid Flow Parametersmentioning
confidence: 99%